Selected poems of Shmuel HaNagid - Samuel, ha-Nagid, 993-1056 (Lockert library of poetry in translation., 1996)
The first major poet of the Hebrew literary renaissance of Moslem Spain, Shmuel Ben Yosef Ha-Levi HaNagid (993-1056 C.E.) was also the prime minister of the Moslem state of Granada, battlefield commander of the non-Jewish Granada army, and one of the leading religious figures in a medieval Jewish world that stretched from Andalusia to Baghdad.